(untitled) (Research, Society and Development, 2020)
This article of theoretical-reflexive basis proposes to analyze the historical and epistemological trajectory of the notion of subject inside the French Discourse Analysis theory (DA, from now on). Due to the fact of the heterogeneity which involves this term, the DA which we refer to is that around the studies of the French philosopher Michel Pêcheux ([1975] 1988), and whose constitution receives the useful contributions of Michel Foucault ([1969] 1995) and Authier-Revuz ([1982] 2004, [1983] 1990). Furthermore, as it is an interdisciplinary subject and, thus, makes connections with other fields of study, we will deal with the notion of identity following the contemporary cultural studies (according to Bauman, 2005; Hall, 2006, 2007; Silva, 2007; Woodward, 2007) and how this concept contributes with the subject in the discursive perspective. These articulations serve as a useful tool for researches in DA, whose analysis of corpora deal with the discursive subject directly or indirectly.